Teacher Professionalism in the Shadow of the Law: A Normative Analysis of the Implementation of Law No. 14 of 2005 concerning Teachers and Lecturers - Hadi, Abdul; Abdul Zalil, Muhammad; Hakim, Lukman; Sekar Ayu Safitri, Dewi; Azhar Muttaqin, Muhammad (Jurusan Pendidikan Teknik Elektro, 2026)
This study analyzes the implementation of teacher professionalism under Law No. 14 of 2005 on Teachers and Lecturers through a normative juridical approach, with the objective of identifying normative gaps between legal provisions and their practical enforcement. This research focuses on three critical dimensions of implementation: legal protection in disciplinary practices, regulatory inequality in retirement age between teachers and lecturers, and delays in professional certification through the Professional Teacher Education Program (PPG). The findings demonstrate that teacher professionalism is weakened by inconsistent legal protection against criminalization, structural inequity in retirement regulations, and persistent certification backlogs caused by institutional capacity and administrative barriers. The novelty of this study lies in its integrative normative analysis, which connects statutory provisions with documented legal cases, constitutional review processes, and longitudinal certification data. By systematically mapping these legal vulnerabilities, this study contributes to legal and educational scholarship by offering a structured framework for strengthening regulatory enforcement and institutional accountability in safeguarding teacher professionalism in Indonesia.